Desarrollo neurofuncional en los niños y niñas del Centro de Educación Inicial “Mis Amiguitos" - Jiménez Changoluisa, Yadira Viviana (2021)
The objective of this investigation was to determine the development of the neurofunctional center in the children of the "Mis Amiguitos" taking into account the current Early Childhood Education Center, understanding that neurofunctional development is important in the first years of the infant's life. Methodologically, a quantitative approach was used. The design was non-experimental, descriptive and basic. The population corresponded to preschool infants. The sample consisted of 8 boys and 8 girls from preschool II. The sampling was non-probabilistic and intentional. The technique was the psychometric test, and the instrument was the Cumanín neuropsychological maturity questionnaire, which allowed corroborating the development of the neurofunctional areas, identifying the areas of neurofunctional development in the boys and girls, predominating the verbal and non-verbal areas and the complementary. areas. As they are, verbal fluency, attention and laterality were also analyzed, favoring neurological maturity that facilitates processes of social interaction and learning, and differences in neurofunctional areas; In the verbal areas, articulated language, the results were lower in the girls, in expressive and integral language they presented higher values, but the boys quantified immaturity in both comprehensive and expressive language, it could be deduced that, in non-verbal language development In psychomotor skills and iconic memory, boys and girls obtained higher values, but in their visual perception spatial structure they obtained a lower value; in rhythm, boys were the ones with the lowest scores.